Remember the Hand Manuscription in Early Medieval Iberia - Brown, Catherine (Fordham University Press, 2023)
Remember the Hand studies a body of articulate manuscript books from the Christian monasteries of northern Iberia in the tenth and eleventh centuries. These exceptional, richly illuminated codices have in common an urgent sense of scribal presence-scribes name themselves, describe themselves, even paint their own portraits. While marginal notes, even biographical ones, are a common feature of medieval manuscripts, rarely do scribes make themselves so fully known. These writers address the reader directly, asking for prayers of intercession and sharing of themselves. They ask the reader to join them in not only acknowledging the labor of writing but also in theorizing it through analogy to agricultural work or textile production, tending a garden of knowledge, weaving a text out of words.By mining this corpus of articulate codices (known to a school of Iberian codicologists, but virtually unstudied outside that community), Catherine Brown recovers these scribes' understanding of reading as a powerful, intimate encounter between many parties-authors and their text, scribes and their pen, patrons and their art-object, readers and the words and images before their eyes-all mediated by the material object known as the book. By rendering that mediation conspicuous and reminding us of the labor that necessarily precedes that mediation, the scribes reach out to us across time with a simple but profound directive: Remember the hand.Remember the Hand is available from the publisher on an open-access basis.